Two Canals In Palatal Root Of Maxillary Molar - Dr. Mohammad Ali; Dr. Ahsan Inayat (ziauddin University, 2020)
This article highlights the need to be aware of different morphologies which can exist in the root canal system of maxillary molars. These are usually associated with buccal root and have been documented in several studies in literature. On the other hand, it is not often that we come across variations in the palatal roots. This case discusses such a case where two canals were discovered in palatal root during root canal treatment of maxillary first molar. It is essential to evaluate pre-operative radiographs and have proper knowledge of anatomy of the root canal system before initiating the treatment. Roots should be explored carefully to ensure that all canals are identified, debrided and obturated to ensure successful endodontic outcome.